MXene Lubricated Tribovoltaic Nanogenerator with High Current Output and Long Lifetime - Qiao, Wenyan; Zhou, Linglin; Zhao, Zhihao; Yang, Peiyuan; Liu, Di; Liu, Xiaoru; Liu, Jiaqi; Liu, Dongyang; Wang, Zhong Lin; Wang, Jie (Nano-Micro Letters, 2023)
Tribovoltaic nanogenerators (TVNGs) have the characteristics of high current density, low matched impedance and continuous output, which is expected to solve the problem of power supply for small electronic devices. However, wear occurrence in friction interface will seriously reduce the performance of TVNGs as well as lifetime. Here, we employ MXene solution as lubricate to improve output current density and lifetime of TVNG simultaneously, where a high value of 754 mA m−2 accompanied with a record durability of 90,000 cycles were achieved. By comparing multiple liquid lubricates with different polarity, we show that conductive polar liquid with MXene as additive plays a crucial role in enhancing the electrical output performance and durability of TVNG. Moreover, the universality of MXene solution is well demonstrated in various TVNGs with Cu and P-type Si, and Cu and N-GaAs as material pairs. This work may guide and accelerates the practical application of TVNG in future. Highlights: 1 Successfully solves the key issue of tribovoltaic nanogenerators (TVNGs) lifetime (90,000 cycles) and improves its output current density (754 mA m−2) simultaneously. 2 Conductive polar liquid with MXene as additive is proposed as the dominant factor in enhancing the electrical output performance and durability of TVNG simultaneously. 3 The mechanism of lubricated TVNG with enhanced output performance is explained from the perspective of solution polarity at the first time. 4 Mxene solution exhibits universality in different types of semiconductor systems (Cu and P-type Si, and Cu and N-GaAs as material pairs).